Rare case of thoracic endometriosis presenting with lung nodules and pneumothorax. (9th March 2018) - Gates, Jessica; Sharma, Akhilesh; Kumar, Arunesh
Abstract : We present the case of a 34-year-old Nigerian woman who was referred to the Respiratory team with a 12-month history of breathlessness. She was concurrently being investigated for an abdominal mass and rectal and vaginal bleeding. Consequently, she underwent cross-sectional imaging of her chest, abdomen and pelvis, revealing a small right-sided pneumothorax and right lower lobe pleural-based lesion. Shortly thereafter, she was admitted to the hospital with chest pain and required chest drain insertion. This partially treated her pneumothorax but she required referral to a cardiothoracic centre for definitive diagnosis and to manage her non-resolving pneumothorax. Biopsies from the video-assisted thoracoscopic surgery confirmed the very rare diagnosis of thoracic endometriosis.